Transition Curves for Highway Geometric Design - Kobryń, Andrzej (Springer Tracts on Transportation and Traffic, 2017)
This book provides concise descriptions of the various solutions of transition curves, which can be used in geometric design of roads and highways. It presents mathematical methods and curvature functions for defining transition curves. .